A study on Long-term orientation, Self-Efficacy and Self-derogation of Kudumbashree members with special reference to Self Help Group in Kerala (International Journal of Scientific Research and Management (IJSRM), 2015)
In the amount of post Indian Independence, the govt. developed the community development programmers specializing in socio-economic and political management of the folks. Without considering the psychological management of the mass a development programmer cannot accomplish its full potential. Self-efficacy is associate degree inevitable consider psychological empowerment, and at identical time self-derogation can have an effect on psychological management negatively. During this study these 2 variables accustomed live the impact of Kudumbashree project “Poverty demolition Mission” below Kerala Government in its members. The study revealed that the Kudumbashree members have higher self-efficacy and fewer self-derogations than the non beneficiaries of Kudumbashree. There’s correlation statistics between self-efficacy and self-derogation